Periodisation and conditioning: a contemporary approach - Pyne, D. (2006)
Good planning is one of the key elements of effective coaching and should be considered as a skill that must be learned, developed and practiced. Planning integrates the various aspects of training that contribute to swimming performance: swimming technique (skill), physical conditioning (fitness), mental skills training (psychology), as well as racing and training strategies. The topics addressed in this article include: physiological models of exercise and fatigue, the division of the training plan into macro-, meso- and micro-cycles, and description of the various stages or phases of the training plan. One approach is to use a `top-down` process by initially examining the end product: how fast do you need to swim to win?